Nonstationary extreme precipitation in Brazil (2022)
This study provides the first estimates of the frequency distribution of observational and future maximum daily precipitation considering nonstationarity for the entire Brazilian territory. We assess observational data from 1980 to 2015 and projected data from 2020 to 2099 for two climate change scenarios and four downscaled climate models. We modelled extreme precipitation according to the extreme values theory and calculated the precipitation intensity associated with the return periods of 5, 10, 25, 50, and 100 years in nonstationary conditions. The results indicate that nonstationarity is identified in 17.5% of the study area during 1980–2015. The analysis of future climate projections indicated an increase in the return levels of extreme precipitation compared to the historical period in at least 90% of the national territory. It shows that engineering design must urgently consider the nonstationarity of extreme precipitation under the risk of increasingly unsafe infrastructure.